Some Comments on the Literary Activities of Sharof Rashidov - Sulaymonova, Shohsanam (European Journal of Life Safety and Stability (2660-9630), 2022)
The article deals with the students years of the statesman, writer, ardent son of our people Sharof Rashidov, his work in local and national newspapers, his courage in the war, lyrical and prose works as a poet and writer, richness of the main idea and content of the works. The following information is provided.